RUSSIA'S STRATEGIC DETERRENCE AND DEFENSE AGAINST POTENTIAL MEANS AND METHODS OF STRATEGIC ATTACK - A. I. Podberezkin; A. V. Zhukov (Vestnik MGIMO-Universiteta, 2019)
Thе article analyzes the concept of strategic stability and its contemporary development in domestic military-political thought. The authors note that the expansion of the meaningful content of the concept of strategic stability in the Russian Federation occurred as a result of the development of strategic non-nuclear deterrence forces and the US policy to reduce the dependence of American foreign and defense policy on the factor of nuclear deterrence. These changes in the military-political situation in the world have led to a reduction in the stability of the relations of key states, despite some proliferation of nuclear weapon technologies in Asian countries.The article attempts to prove that the Russian Federation is able to withstand the new challenges associated with qualitative changes in the relations of mutual deterrence with the United States. As to this, the authors consistently analyze the historical context and conceptual foundations of deterrence policy, including recent documents adopted at the highest level in Russia. In addition, the authors analyze the recently adopted cruise missile systems in Russia and the United States, as well as anti-missile defense systems that alter the balance of power for a guaranteed response to strategic nuclear forces. Taking into account the current technological developments and the timeline for their implementation, the authors conclude that Russia has been able to achieve significant results in the field of aerospace defense, while naval defense and the introduction of new means of nuclear weapon delivery need additional attention from authorities. Finally, the authors believe that the development of the domestic military-industrial complex directly depends on the country's economic development, which means that the degree of effectiveness of Russian strategic weapons system must remain significantly higher than that of foreign counterparts.